Development of diagnostic assessment using the I Spring Suite Application in Pancasila Learning in Class V Elementary Schools in Region I, West Padang District - Hafidh, Muhenda; Hendrizal, Hendrizal; Ismira, Ismira (Journal of Educational Sciences, 2025)
This type of research is development research (R&D) using the 4D model (Define, Design, Develop, Disseminate). The subjects of the study were 3 experts (media experts, material experts, and language experts), 3 teachers, and fifth grade students at SDN 22 Ujung Gurun, SDN 24 Ujung Gurun, and SDN 05 Padang Pasir. The validation results showed a validity level of 93.75% from media experts, 88.63% from material experts, and 90.6% from language experts, all of which were included in the "very valid" category. Based on the results of teacher and student responses, it is known that the percentage of practicality of learning media at SDN 22 Ujung Gurun reached 92.15% student responses and 95.8% teacher responses, at SDN 24 Ujung Gurun 95.35% student responses and 91.6% teachers, and at SDN 05 Padang Pasir 87.5% students and 95.5% teachers. In addition, the results of the effectiveness test showed an N-Gain value of 0.8054 at SDN 05 Padang Pasir and 0.7825 at SDN 24 Ujung Gurun, including the high category. Thus, it can be concluded that the diagnostic assessment based on i spring suite has been valid, practical, and effective for use in Pancasila learning for grade V elementary school